IDEOLOGI DALAM LITERATUR KEAGAMAAN PADA AKTIVIS DAKWAH KAMPUS DAN KAJIAN ISLAM DI ITB BANDUNG THE Ideology and Transmission of Religious Literature in Da’wah Activists and Islamic Studies in ITB Bandung - Agus Iswanto (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
The religious teaching including ideology is effectively transmitted through literature. The ideology of dakwah movement in campuses can be mapped using their accessed literatures. This study aims to explain the ideology and the transmission of literature that are read and used by two da’wah organizations at campus and Islamic studies in ITB Bandung. The data collection is done with a series of interviews and a review of the text. Interviews were conducted with key informants, consisting of the chairman and the board of the organizations. The results showed that religious literature in the Islamic da’wah activists and Islamic studies is still dominated by authors affiliated with the Muslim Brotherhood (Ikhwan alMuslimin) and the caliphate ideology. Although religious readings are thick with ideology, readers should not be ‘ideological readers,’ because a social network has more influence on the transmission of literature than other factors. Therefore, this seems to be a routine activity without discourse and reading material enrichment.